Prevalence, Pattern and Outcome of Congenital Anomalies in Patients Admitted at a Tertiary Level Hospital in Bangladesh - Podder, Ratna; Zeba, Dilruba; Fatema, Kaneez; Alam, Samiya; Bilkis, Rabeya (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Congenital anomalies are a major public health concern globally, contributing significantly to perinatal and neonatal mortality. Understanding their prevalence, patterns, and outcomes are essential for effective healthcare planning and interventions. This cross-sectional observational study aimed to investigate the distribution and immediate outcomes of congenital anomalies among infants delivered at Bangabandhu Sheikh Mujib Medical College Hospital, Faridpur, Bangladesh. Study population comprised admitted pregnant mothers who delivered infants with congenital anomalies from January to December 2022. Data were collected from medical records, including parity, gestational age at delivery, mode of delivery and outcomes of congenital anomalies. Total 3461 deliveries occurred during this period, of which 88 had congenital anomalies with a prevalence of 2.54%. Among the 88 infants with congenital anomalies, the most prevalent anomalies were Anencephaly and Hydrocephalus, affecting the central nervous system. Anencephaly had a 100% mortality rate, emphasizing its severity and poor prognosis. Anencephaly was more common in infants delivered between 12 to 28 weeks. Early gestational stages play critical role in its pathogenesis. Hydrocephalus showed a relatively higher proportion of live births. Vaginal delivery was the predominant mode of delivery for most congenital anomalies. Public health efforts targeting early detection, appropriate care and support for affected families can potentially reduce the impact of congenital anomalies on maternal and neonatal health. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(1):27-31